Mechanism of Lactiplantibacillus plantarum regulating Ca2+ affecting the replication of PEDV in small intestinal epithelial cells - Kan, Zifei; Zhang, Shujuan; Liao, Guisong; Niu, Zheng; Liu, Xiangyang; Sun, Zhiwei; Hu, Xia; Zhang, Yiling; Xu, Shasha; Zhang, Jingyi; Zou, Hong; Zhang, Xingcui; et al. (Frontiers in Microbiology, 2023)
Porcine epidemic diarrhea virus (PEDV) mainly invades the small intestine and promotes an inflammatory response, eventually leading to severe diarrhea, vomiting, dehydration and even death of piglets, which seriously threatens the economic development of pig farming. In recent years, researchers have found that probiotics can improve the intestinal microenvironment and reduce diarrhea. At the same time, certain probiotics have been shown to have antiviral effects; however, their mechanisms are different. Herein, we aimed to investigate the inhibitory effect of Lactiplantibacillus plantarum supernatant (LP-1S) on PEDV and its mechanism. We used IPEC-J2 cells as a model to assess the inhibitory effect of LP-1S on PEDV and to further investigate the relationship between LP-1S, Ca 2+ , and PEDV. The results showed that a divalent cation chelating agent (EGTA) and calcium channel inhibitors (Bepridil hydrochloride and BAPTA-acetoxymethylate) could inhibit PEDV proliferation while effectively reducing the intracellular Ca 2+ concentration. Furthermore, LP-1S could reduce PEDV-induced loss of calcium channel proteins (TRPV6 and PMCA1b), alleviate intracellular Ca 2+ accumulation caused by PEDV infection, and promote the balance of intra-and extracellular Ca 2+ concentrations, thereby inhibiting PEDV proliferation. In summary, we found that LP-1S has potential therapeutic value against PEDV, which is realized by modulating Ca 2+ . This provides a potential new drug to treat PEDV infection..